2022
DOI: 10.1155/2022/4268681
|View full text |Cite|
|
Sign up to set email alerts
|

TCM Treatment and Drug Co-Occurrence Analysis of Psoriasis

Abstract: Psoriasis is a long-term immune-mediated disease. Patients with a long history and slow progress are more common, and its treatment is difficult. This study proposes to use traditional Chinese medicine to treat psoriasis. Through the follow-up of all participants for 12 and 24 weeks, a large number of comparative experiments effectively verify the effectiveness of the method proposed in this study. The research results of this study can provide some reference ideas for follow-up research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…According to traditional Chinese medicine, psoriasis is mainly divided into three types of syndromes (blood heat, blood stasis and blood dryness), so psoriasis is mainly treated from the blood [43]. And herbs with the effect of dispersing blood stasis or cooling blood such as Curcuma Aeruginosa Roxb, Radix Paeoniae Rubra, Radix Angelicae Sinensis, Indigo Naturalis, Rubix Rubiae etc are frequently appeared at the prescriptions as the main herb when treating psoriasis [44][45][46]. PSORI is a cipher prescription our hospital used to treat psoriasis for many years [44,48], it contained two kinds of drugs, one is herbs with dispersing blood stasis effect and the other is with the effect of clearing heat-toxin, when compared their effect on psoriasis in mice model, the results showed that dispersing blood stasis drugs showed a better effect [49], and this is accorded with the theory of traditional Chinese Medince and the results of manuscript.…”
Section: Discussionmentioning
confidence: 99%
“…According to traditional Chinese medicine, psoriasis is mainly divided into three types of syndromes (blood heat, blood stasis and blood dryness), so psoriasis is mainly treated from the blood [43]. And herbs with the effect of dispersing blood stasis or cooling blood such as Curcuma Aeruginosa Roxb, Radix Paeoniae Rubra, Radix Angelicae Sinensis, Indigo Naturalis, Rubix Rubiae etc are frequently appeared at the prescriptions as the main herb when treating psoriasis [44][45][46]. PSORI is a cipher prescription our hospital used to treat psoriasis for many years [44,48], it contained two kinds of drugs, one is herbs with dispersing blood stasis effect and the other is with the effect of clearing heat-toxin, when compared their effect on psoriasis in mice model, the results showed that dispersing blood stasis drugs showed a better effect [49], and this is accorded with the theory of traditional Chinese Medince and the results of manuscript.…”
Section: Discussionmentioning
confidence: 99%
“…It focuses on a holistic view that combines evidence differentiation with treatment methods, appropriate coordination of the 3 methods, flexible treatment methods, low side effects, and low recurrence rates after clinical cure. [9,10] Fire needle therapy has the characteristics of simplicity, convenience, testing, and integrity and is an important part of the traditional characteristic therapy of TCM. [11] In ancient times, it was also called "thorn" and "burnt needle," which specifically refers to the tip of the needle after burning red and quickly stabbed into the acupoint.…”
Section: The Authors Have No Conflicts Of Interest To Disclosementioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%